Doctor-diagnosed sleep disorders in the United States: Prevalence and impact of tobacco smoke exposure and vitamin D deficiency. A population-based study - Kum-Nji, Philip; Taylor, Samuel; Tanwi, Bah (Frontiers in Sleep, 2023)
Background and Purpose. We determined the prevalence of physician-diagnosed sleep disorder and its association with tobacco smoke exposure and vitamin D deficiency. Methods. The National Health and Nutrition Examination Survey (NHANES) of 2011-2012 data base was used for the study. Subjects were asked two questions: “Ever told your doctor you had trouble sleeping?” and “Ever told by doctor have sleep disorder?” The answer “yes”to the second question indicated presence of a doctor-diagnosed sleep disorder (DSD) and “no” indicated its absence. Tobacco smoke exposure was defined by serum cotinine levels while vitamin D levels were measured by serum 25(OH) D. Eight selected variables included in the analyses were BMI, age, gender, smoking exposure, vitamin D levels, income, insurance, and race. Univariate and multivariate analyses were conducted to determine if tobacco smoke exposure and Vitamin D were each predictive of DSD. Results. Of 5,470 subjected aged 16 to 80+ years about 9% had doctor-diagnosed sleep disorder (DSD). In a multiple regression analysis, active tobacco smoking was predictive of DSD (OR 1.92; 95% CI=1.38-2.69), while passive smoke exposure was not, even after controlling for all the other significant variables (OR 0.93; 95% CI=0.57-1.52). The other variables significantly associated with DSD were by order of importance BMI (P<0.001), Age (P<0.001) and race (P=<0.001). Vitamin D deficiency was not predictive of DSD. Conclusion. The prevalence of physician-diagnosed DSD was about 9%. Active smoking but not passive smoking as defined by cotinine levels was significantly associated with DSD. Vitamin D was not predictive of DSD. Future studies are therefore needed to demonstrate whether smoking cessation could help reduce DSD.